2014
DOI: 10.1186/1471-2458-14-932
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic differences in childhood length/height trajectories in a middle-income country: a cohort study

Abstract: BackgroundSocioeconomic disadvantage is associated with shorter adult stature. Few studies have examined socioeconomic differences in stature from birth to childhood and the mechanisms involved, particularly in middle-income former Soviet settings.MethodsThe sample included 12,463 Belarusian children (73% of the original cohort) born in 1996–1997, with up to 14 stature measurements from birth to 7 years. Linear spline multi-level models with 3 knots at 3, 12 and 34 months were used to analyse birth length and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
(68 reference statements)
0
19
0
Order By: Relevance
“…Consistent with this position, Galobardes et al 31 found that midparental height (average of mother and father’s height) fully explained the initial difference in children’s height. Others by contrast have found that parental height is not a sufficient explanation for socioeconomic differences in height,18 although the latter study is from a low-income to middle-income country. In any event, one could argue that this explanation is not particularly convincing because it simply shifts the debate back a generation and makes one query whether it was more advantageous environmental exposures in the parent’s generation that led to the development of taller parents (ie, intergenerational reproduction of inequalities).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Consistent with this position, Galobardes et al 31 found that midparental height (average of mother and father’s height) fully explained the initial difference in children’s height. Others by contrast have found that parental height is not a sufficient explanation for socioeconomic differences in height,18 although the latter study is from a low-income to middle-income country. In any event, one could argue that this explanation is not particularly convincing because it simply shifts the debate back a generation and makes one query whether it was more advantageous environmental exposures in the parent’s generation that led to the development of taller parents (ie, intergenerational reproduction of inequalities).…”
Section: Discussionmentioning
confidence: 72%
“…Although, studies have shown that social inequalities in children’s length/height are already apparent at time of birth, it remains unclear whether the differences remain stable,9 narrow11 or widen18 as children age. Furthermore, many of the recent studies are based on relatively old data from British cohorts 9–11 19.…”
Section: Introductionmentioning
confidence: 99%
“…We parameterized the relationships of weight, stature or BMI z-score with age using linear splines with 5 knot points at 3 months, 12 months, 2.8 years, 8.5 years and 14.5 years to describe periods of approximately linear growth based on the data. (38) Although a linear spline model is an approximation of the true non-linear growth function, its coefficients are easily interpretable and have produced a good model fit in this and other cohorts. (3944) The knot points at 8.5 and 14.5 years were chosen because those were the oldest ages at the 6.5- and 11.5-year follow-ups.…”
Section: Methodsmentioning
confidence: 99%
“…Studies from the Netherlands, Australia and the UK found no association between infant growth and SEP [104,105,108] (with the Australian study assessing rapid infant weight gain), with four European studies from the UK, Netherlands and Sweden finding an inverse association [106,107,109,110] (Wiljaars finding an association with rapid weight gain and Svensson finding an association with overall weight gain but not rapid weight gain). Only two studies were conducted in low-or middle-income countries, with a positive association observed in infants from both Belarus [111] and Chile (noting that the Chilean sample excluded babies <3 kg at birth) [112].…”
Section: Rapid Infant Growth and Early Adiposity Reboundmentioning
confidence: 99%